A population-based assessment of metastatic hepatoblastoma in Texas reveals ethnic disparities - Espinoza, Andres F.; Scheurer, Michael E.; Chambers, Tiffany M.; Vasudevan, Sanjeev A.; Lupo, Philip J. (Frontiers in Public Health, 2023)
Background Hepatoblastoma (HB) is the most common primary liver cancer in children with emerging evidence that incidence is increasing globally. While overall survival for low risk hepatoblastoma is >90%, children with metastatic disease have worse survival. As identifying factors associated with high-risk disease is critical for improving outcomes for these children, a need for a further understanding of the epidemiology of hepatoblastoma is warranted. Therefore, we conducted a population-based epidemiologic study of hepatoblastoma in Texas, a large state characterized by ethnic and geographic diversity. Methods Information on children diagnosed with hepatoblastoma at 0–19 years of age for the period of 1995–2018 was obtained from the Texas Cancer Registry (TCR). Demographic and clinical variables including sex, race/ethnicity, age at diagnosis, urban-rural status, and residence along the Texas-Mexico border were evaluated. Multivariable Poisson regression was used to calculate adjusted incidence rate ratios (aIRRs) and 95% confidence intervals (CIs) for each variable of interest. Joinpoint regression analysis was used to determine the trend in incidence of hepatoblastoma, overall and by ethnicity. Results Overall, 309 children diagnosed with hepatoblastoma in Texas for the period of 1995–2018. Joinpoint regression analysis showed no joinpoints in the overall or the ethnic-specific analyses. Over this period, the incidence increased at 4.59% annually; with the annual percent change higher among Latinos (5.12%) compared to non-Latinos (3.15%). Among these children, 57 (18%) had metastatic disease at diagnosis. Factors associated with hepatoblastoma included male sex (aIRR = 1.5, 95% CI: 1.2–1.8, p = 0.002); infancy (aIRR = 7.6, 95% CI: 6.0–9.7, p < 0.001); and Latino ethnicity (aIRR = 1.3, 95% CI: 1.0–1.7, p = 0.04). Additionally, children living in rural areas were less likely to develop hepatoblastoma (aIRR = 0.6, 95% CI: 0.4–1.0, p = 0.03). While residence on the Texas-Mexico border association with hepatoblastoma approached statistical significance (p = 0.06) in unadjusted models, this finding did not remain significant after adjusting for Latino ethnicity. The two factors associated with being diagnosed with metastatic hepatoblastoma included Latino ethnicity (aIRR = 2.1, 95% CI: 1.1–3.8, p = 0.02) and male sex (aIRR = 2.4, 95% CI: 1.3–4.3, p = 0.003). Conclusions In this large population-based study of hepatoblastoma, we found several factors associated with hepatoblastoma and metastatic disease. The reasons for a higher burden of hepatoblastoma among Latino children is unclear but could be due to differences in geographic genetic ancestry, environmental exposures, or other unmeasured factors. Additionally, it is notable that Latino children were also more likely to be diagnosed with metastatic hepatoblastoma compared to non-Latino white children. To our knowledge, this has not been previously reported and warrants further study to delineate the causes of this disparity and identify interventions to improve outcomes.